Asia-Pacific Free Trade Talks nearing the finish line: Setting the agenda in the struggle for regional markets, multilateral rules and geopolitical leadership - Hanns Günther Hilpert (Stiftung Wissenschaft und Politik (SWP), 2015)
Asia is not only the world's most dynamic region in terms of trade, it is also an important pacesetter in trade policy. The US is currently negotiating with eleven partner countries over a Trans-Pacific Partnership (TPP); the members of the ASEAN+6 group are in talks over a Regional Comprehensive Economic Partnership (RCEP); while Japan, China and Korea are conducting trilateral trade negotiations (CJK FTA). The multilateral structures emerging from all these initiatives could, in the long term, be combined into a Free Trade Area of the Asia-Pacific (FTAAP). What are the motives behind these agreements? What are their chances of being implemented? When it comes to the trade and geopolitical power struggle that encompasses these talks, does the US or China have the upper hand? And what role remains for Europe's trade policy? (SWP Comments)
Keywords: 320